Analysis of Validity Coefficient For Factor Scores Against Teacher Ratings In Spiritual Intelligence: - (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The verbal testwhich has been described in the present material is part of the total batterywhich consists of both verbal and non-verbal tests. The verbal test ofcreativity includes four subtests namely consequences test, unusualness test,similarity test and product improvement test. The totaltime required for administering the test is 48 minutes in addition to  the time  necessary  for giving  instructions,  passing out  tests  booklets to children and collecting them back. In thepresent investigation the Llkert's (1932) Amethod has been followed which ismore convenient as far as administrative, economic and time facilities areconcerned. The investigator prepared 39 statements which are related toreligion. The statements of the scale have the following features: i)              All the statements are related toreligion. ii)             All the statements are to be markedon a live point rating scale. iii)             The statements are simple, specific and clear. iv)         The statements are in the form ofopinions rather than a narration of facts. Appropriateinstructions have been given in the scale.